2016
DOI: 10.1210/en.2015-1966
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Within the Subphysiological to Physiological Range Dose Dependently Improves Male Reproductive Function in an Obesity Mouse Model

Abstract: Obesity has recently been linked with reduced fertility, and the mechanisms underpinning this effect are currently unknown. The adipokine leptin is dysregulated in obesity and affects reproductive tracts; therefore, we investigated the dose-dependent effects of leptin on Leydig cell function and spermatogenesis. Eight-week-old leptin-deficient obese (ob/ob) male mice were treated with subphysiological (0.1- or 0.5-mg/kg body weight [BW]/d) or physiological (3.0-mg/kg BW/d) doses of leptin or saline for 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…In addition to adipose-derived leptin, testicular leptin regulates T production from Leydig cells through its ability to regulate steroidogenic enzymes [2, 33, 34]. Furthermore, obesity-associated hyperleptinemia negatively impacts testicular function and T production in males [3537].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to adipose-derived leptin, testicular leptin regulates T production from Leydig cells through its ability to regulate steroidogenic enzymes [2, 33, 34]. Furthermore, obesity-associated hyperleptinemia negatively impacts testicular function and T production in males [3537].…”
Section: Resultsmentioning
confidence: 99%
“…For example, mice with congenital deficiency of leptin ( ob/ob mice) exhibit hyperphagia, reduced energy expenditure, obesity, and infertility [41]. Administration of leptin to ob/ob mice restores their fertility [33, 42, 43], and in normal animals, it can advance puberty onset [44]. On the other hand, deregulated leptin production, especially at an early developmental stage, can have detrimental effects on the maturation and function of the HPG axis [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DM1, in humans and experimental animals the plasma levels of leptin are decreased significantly (Kraus, Herman, & Kahn, 2010), and a leptin deficiency leads to the reduced testicular activity (Martins, Aguila, & Mandarim‐de‐Lacerda, 2017). Since leptin has a significant effect on the steroidogenesis and spermatogenesis (Hoffmann et al, 2016; Shpakov, Ryzhov, Bakhtyukov, & Derkach, 2018), the leptin monotherapy causes their improvement in DM1 (Schoeller et al, 2014). However, there is less information available on the intratesticular expression of leptin and its receptor in the conditions of DM1.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, leptin-deficient ob/ob mice, in which leptin’s effect are absent, exhibit either decreased 18, 19 , increased 20, 21 , or unchanged 22 adiponectin circulating concentrations. Moreover, many previous studies have used supraphysiological or even pharmacological doses of leptin 18, 23 that may overestimate its effects or, alternatively, exert no effect since it has been reported that pharmacological doses of leptin may lose its effect due to saturation or downregulation of receptors 24 or even elicit opposite effects to those observed after the administration of a low leptin dose around the physiological level 25 .…”
Section: Introductionmentioning
confidence: 99%